The Moderation Role of Tax Socialization on Tax Knowledge and Implementation of the E-Filling System on Taxpayer Compliance (Universitas Terbuka, 2025)
This study aims to obtain empirical evidence of the influence of tax knowledge and the application of the e-Filing system on taxpayer compliance with moderation of tax socialization. In this study, samples were taken from individual taxpayers of KPP Pratama Surabaya Gubeng using the purposive sampling method. The analysis used in this study is multiple linear regression analysis and moderation regression analysis (MRA). The results of the study found that there was a positive influence between tax knowledge on taxpayer compliance. The implementation of the e-Filing system also has a positive effect on taxpayer compliance. In contrast to tax socialization which is unable to moderate the influence of tax knowledge and the application of the e-Filing system on the compliance of individual taxpayers of KPP Pratama Surabaya Gubeng.